Financial Evaluation of Photovoltaic Energy Projects in Colombia (2020)
The use of renewable sources, especially photovoltaics, has become a viable alternative as a supply of this vital element without destroying the environmental environment. In this sense, the main objective of the study is to propose a methodology of economic/financial evaluation of photovoltaic energy projects in Colombia, through the application of the real options valuation, the above supported by a mixed method that combines the review of qualitative information or documentary in conjunction with a quantitative sample based on numerical data and official figures, in order to address the issue with rigorous livelihoods. The results indicate that the photovoltaic energy has a high potential in the country, according to the real options valuation the total investment cost of the installation and commissioning for a 5000 Kw plant would be $ 18,930,000 USD, taking advantage of 1825 h of work thus generating about 9,125,000 Kw/h. It is concluded that the energy matrix in Colombia must be diversified, supported by a government management that facilitates access to credit lines that leverage the initial investment in capital, additionally, taking advantage of the geographical characteristics of Guajira, Magdalena and the Atlantic is crucial for Implement these types of projects.